Worrying cadmium and lead levels in a commonly cultivated vegetable irrigated with river water in Zimbabwe. Issue 1 (1st January 2020) - Tibugari, Handsen; Mafere, Gerald; Dube, Sinikiwe; Chakavarika, Murawu; Mandumbu, Ronald; Musara, Joseph P.; Mapuranga, Rangarirai; Gumbo, Tapiwa; Annabel, Banda; Mathema, Ndabanye; Goche, Tatenda; Bernard M., Zvigumbu; et al.
Abstract: Vegetable cultivation using river water, which may be polluted with heavy metals, can cause health problems to consumers. A study to establish cadmium and lead levels in water from Msasa, Manyame; Mukuvisi and Nyatsime Rivers was conducted in 2019. A questionnaire survey involving 105 randomly selected urban vegetable growers was conducted to examine farmer knowledge of the potential of polluted water to contaminate produce through heavy metals. Water, soil and vegetable samples were also collected and analysed for heavy metal presence using atomic absorption spectrophotometry. Results showed that some farmers (62%) were aware that wastewater could contain heavy metals. The majority of farmers (67%) applied phosphate-based fertilisers, a potential source of cadmium. Tested at P < 0.05, the results showed that sampled water from the four sites failed to meet the Standards Association of Zimbabwe 5560 (1997) standards. Cadmium tissue concentration from wastewater from Msasa and Manyame rivers was 1.3 and 1.17 mg g −1 respectively, which were 59 and 65 times higher than 0.02 mg g −1 from the control. Water from Manyame and Nyatsime rivers contains levels of heavy metals which exceed the Environmental Management Agency (EMA) safety guidelines. Farmers need to be educated on health hazards from contaminated wastewater. Enforcing regulations on effluent disposal, licencing of vegetable vendors and labelling of vegetables with information on source of water used to irrigate the crop can help reduce exposure of unsuspecting vegetable consumers.